A qualitative examination of the relationship between rumination, distress, and dysregulated behaviours in vulnerable young people. (27th July 2020) - Sloan, Elise; Moulding, Richard; Weiner, Carlye; Dowling, Rose‐Mary; Hall, Kate
Abstract : Objectives: Young people accessing mental health treatment in Australia frequently engage in dysregulated behaviours, such as substance misuse, deliberate self‐harm (DSH), and binge eating and purging. Rumination has been identified as a correlate of behavioural dysregulation; however, a qualitative examination of the functional relationship between ruminative processes and distress and subsequent engagement in dysregulated behaviours has not yet been conducted. This study aimed to explore the characteristics of rumination in young people and examine how this process relates to engagement in DSH, binge eating and purging, and substance misuse in a sample of treatment‐seeking young people. Design: A qualitative research methodology was used gain an in‐depth understanding of participants' experience of rumination as it relates to their engagement in dysregulated behaviours. Methods: Twelve treatment‐seeking young people were interviewed about their experience of rumination in the context of a recently recalled situation where they engaged in a dysregulated behaviour. Interview data were analysed using thematic analysis. Results: Themes included the following: (1) triggers to behavioural dysregulation; (2) characteristics and content of rumination; (3) key precipitants to dysregulated behaviours (rumination, distress, and prior ineffective were at managing rumination); and (4) distraction from rumination and regulation of distress as short term, positively reinforcing consequences of dysregulated behaviours, while ongoing cycles of rumination and psychological distress were identified as long‐term consequences. Conclusions: DSH, binge/purge behaviours, and substance misuse represent maladaptive ways to distract from intense and pervasive rumination in this cohort of young people. Theoretical and treatment implications pertaining to these findings are discussed. Practitioner points: Rumination is a common experience in young people who engage in dysregulated behaviours including deliberate self‐harm, binging and purging, and substance misuse Engagement in behavioural dysregulation functions to distract from rumination, which negatively reinforces further engagement in dysregulated behaviours. Interventions in this population should focus on the development of adaptive skills that provide the same level of distraction provided by the physical sensations associated with engaging in a dysregulated behaviour.